Understanding the success factors of MOOCs' retention intention: A Necessary Condition Analysis. - Zhang Huacui; Md Nahin Hossain; Kong Zhen; Nilesh Kumar (PLoS ONE)
This paper seeks to explore the influence of success factors, specifically motivation and course quality, on MOOC retention intention. Going beyond a mere examination of these motivational and quality factors, the study investigates students' motivation, considering needs, interests, course system, content, and service quality. Methodologically, a questionnaire survey was conducted, collecting data from 311 students enrolled in online courses. To ascertain the impact of interest or need-based motivation on students' retention rates, a Structural Equation Model (SEM) was employed. Subsequently, Necessary Condition Analysis (NCA) was utilized to identify the essential factors and components in each area. SEM results revealed a positive influence of motivational factors and quality issues on students' behavior. Retention behavior was notably affected by academic and professional needs, along with personal interests. Furthermore, course content and service quality demonstrated a significant effect on students' perseverance behavior. NCA results identified academic motivation and system quality as having a substantial impact on retention behavior, while personal motivation and technological motivation had a comparatively smaller effect. Practically, the findings suggest that course developers should consider students' academic and personal requirements when designing online courses. Additionally, providing students with the ability to customize course and system content according to their needs is crucial. Timely problem-solving attitudes from service providers are essential for ensuring student retention.